Effects of Branch Content and Branch Length on Polyethylene Crystallization: Molecular Dynamics Simulation. Issue 3 (23rd April 2016) - Gao, Rui; He, Xuelian; Shao, Yunqi; Hu, Yanling; Zhang, Haiyang; Liu, Zhen; Liu, Boping
Abstract : Effects of branch length and content on polyethylene crystallization are investigated by molecular dynamics simulation. Branch content greatly influences both crystallization kinetics and morphologies. Final morphologies change from lamellae crystal to bundle crystal as branch content increases. Branch length mainly affects conformational changes as branch inclusion happens. Trans ‐rich phenomenon in pre‐crystalline state is observed by using logarithm scale of time. Abstract : Influences of branch content (BC) and branch length (BL) on isothermal crystallization of precisely branched polyethylene are studied by molecular dynamics simulation. Branch acts as a defect both in nucleation and crystal growth process. BC affects not only crystallization kinetics but also final morphologies. Crystallization rate and crystallinity decrease as BC increases. Morphology Regimes change from lamellae crystal to bundle crystal at critical BC (20/1000 C) because of different folding pattern. 50 CH2 is the critical methyl sequence length to form lamellae crystal. Lamellae thicknesses of final morphologies decrease in gradient corresponding to Morphologies Regimes. BL has no influence on the crystallization kinetics, and only affects the final morphologies when more branches inclusion happens with BL increasing. Trans ‐rich phenomenon in pre‐crystalline state is observed. Crystallization process begins at the end of induction stage when trans state population reaches a critical value, and this value is independent of BC and BL.